Not All Migrants Are the Same: Decent Work and Pre- and Post-Migration Experiences of Economic Migrants - Maha Yomn Sbaa; Simone Donati; Salvatore Zappalà (Social Sciences)
Grounded in the dual frame of reference theory and a life-course perspective, this study explores how migrants’ past work experiences shape the perceptions of their actual work in the host country. The study examines pre- and post-migration working conditions and life satisfaction and compares them to perceptions of decent work (DW). Additionally, the study also compares the DW perceptions of migrants with prior work experience in their home country with those of migrants who lack such experience and started to work in the host country. Using the Decent Work Questionnaire (DWQ), the study analyzes responses from 137 participants. A two-step cluster analysis identified three distinct groups of migrants living in Italy with pre-migration work experience in their home country. These clusters have been labeled as follows: (1) “Better Life, Better Work”, (2) “Better Life, Worse Work”, and (3) “Same Life, Worse Work”. ANOVA results showed that the better life, better work group reported significantly higher overall DW perceptions, as well as higher scores on five out of the seven dimensions of the DWQ. Socio-demographic characteristics were further analyzed to explain variations across clusters. These findings highlight the complex interplay between pre- and post-migration experiences and their impact on migrants’ DW perceptions in their current roles. Additionally, such clusters were compared with a control group that does not have prior work experience in the home country. Results suggest that time-sensitive factors but also other factors, such as expectations, may determine those perceptions. Finally, the study offers practical recommendations for improving workplace conditions and provides insights for organizations and policymakers aiming to better support economic migrants’ integration in the workplaces.